2017
DOI: 10.1556/2006.6.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Gambling disorder: Association between duration of illness, clinical, and neurocognitive variables

Abstract: Background and aimsGambling disorder (GD) may have its onset in a wide range of ages, from adolescents to old adults. In addition, individuals with GD tend to seek treatment at different moments in their lives. As a result of these characteristics (variable age at onset and variable age at treatment seeking), we find subjects with diverse duration of illness (DOI) in clinical practice. DOI is an important but relatively understudied factor in GD. Our objective was to investigate clinical and neurocognitive cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Despite the use of heterogeneous and generalist QOL/HRQOL measurement instruments, observational studies found that pathological and problem gamblers were more impacted than controls in QOL (Black et al, 2013;Chamberlain et al, 2016;Ekholm et al, 2018;Grant and Kim, 2005;Kohler, 2014;Medeiros et al, 2016;Mythily et al, 2011;Scherrer JF et al, 2005). The duration of illness was also correlated with QOL (Medeiros et al, 2017). Some sub-scores on the scales, particularly SF scale, were not significant: physical subscale, bodily pain and even social functioning for example (Mason and Arnold, 2007;Morasco and Petry, 2006;Najavits et al, 2010;Scherrer JF et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of heterogeneous and generalist QOL/HRQOL measurement instruments, observational studies found that pathological and problem gamblers were more impacted than controls in QOL (Black et al, 2013;Chamberlain et al, 2016;Ekholm et al, 2018;Grant and Kim, 2005;Kohler, 2014;Medeiros et al, 2016;Mythily et al, 2011;Scherrer JF et al, 2005). The duration of illness was also correlated with QOL (Medeiros et al, 2017). Some sub-scores on the scales, particularly SF scale, were not significant: physical subscale, bodily pain and even social functioning for example (Mason and Arnold, 2007;Morasco and Petry, 2006;Najavits et al, 2010;Scherrer JF et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it remains unclear whether trichotillomania, skin-picking disorder, pyromania or intermittent explosive disorder could be conceived as BA. Therefore, the current classification and diagnosis of BA are to date a matter of ongoing debate ( Ascher and Levounis, 2015 ) yet the evidence is clear that BA are associated with worse clinical outcomes and quality of life ( Medeiros et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, LT2 profile is representative of older individuals who exhibit a typical telescoping effect (addictive related problems develop more quickly than in younger age groups) [92] exacerbated by the typical aging-related cognitive biases [93]. Older individuals constitute a highly -vulnerable group with specific motivations for initiating and persisting in behavioral addictions (such as escaping loneliness and social isolation, relieving tension or coping with anxiety/depression symptoms due to the loss of a loved one or simply relieving boredom in retirement) [94,95]. Cognitive decline and physicalmental illness in older individuals also seem to play a central role in the onset, maintenance and escalation of addictive behaviors [96].…”
Section: Discussionmentioning
confidence: 99%